Concept of information activity of law enforcement bodies - Banach, Serhii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2019)
The article analyzes information support of law enforcement agencies activity. It is proved that in our country it is necessary to improve the interdepartmental system of information provision in accordance with the requirements of international standards. The directions of solving the problems of modern information provision in the organs of internal affairs of Ukraine are proposed.